Science of Rasm Al-Qur'an: Analysis of Developments in the Digital Era - Andi Darmawansyah Sayuti; Achmad Abubakar; Abdul Ghany (Tilawah: Journal of Al-Qur'an Studies, 2025)
The science of Rasm Al-Qur'an is a discipline that discusses the rules of writing the Qur'an that were established during the time of Uthman bin Affan, known as Rasm Utsmani. These rules have been a guideline in writing and reading the Qur'anic manuscripts for centuries, maintaining the integrity of the Qur'anic text. In recent decades, technological developments have brought significant changes in the science of the Qur'an and its interpretation. Digitization and technology have revolutionized the way the Qur'anic manuscripts are written, reproduced, and distributed, making it easier to learn Rasm Al-Qur'an without time limits. This study aims to analyze the development of the science of Rasm Al-Qur'an in the modern era, both theoretically and practically, and to see how this science adapts to technological advances and the needs of contemporary Muslims. The method used is library research, which collects and analyzes data from various sources. The results of this study indicate that digitization not only facilitates ancient manuscripts and standardization of the Qur'anic text. The digital Al-Quran application offers various features that enrich the learning experience, increase people's understanding and interest in studying the science of Rasm Al-Quran.